POTENSI KAMPUNG NELAYAN SEBAGAI MODAL PERMUKIMAN BERKELANJUTAN DI TAMBAKLOROK, KELURAHAN TANJUNG MAS - Sonya Dimitra; Nany Yuliastuti (Jurusan Perencanaan Wilayah dan Kota, 2012)
Kampong Tambaklorok, in Tanjungmas, North Semarang is located in coastal of the Java Sea. Thi Kampong is known because of the existence of TPI (Tempat Pelelangan Ikan). On one hand, this fringe area that develops into residential compound has several problems that is similar with fisherman villages in Indonesia coastal, such as poverty, and inadequate facilities and infrastructures. On the other hand, behind these problems there are some potentials that can be a capital for sustainable settlements. This study examines the potential of Kampong Nelayan Tambaklorok that can be a capital of sustainable settlements. Some analysis are realized to reach the aim of this study: analysis as of quality of the facilities and infrastructure avalabilities, analysis of quality of a residential dwelling, analysis of social and economic condition of the community, and potential Kampong Nelayan analysis as a capital for sustainable settlements. The result of this study shows that Kampong Tambaklorok has not been alleged as a sustainable settlements. But this kampong has social aspects that can be a capital for becoming a sustainable settlements. To conclude, beyond of the problems such as lack of inftrastructure which leads to poverty and slums settlements, this kampong has valuable capital to make it a sustainable settlements.